Nanorod flower-shaped In2O3 material, preparation method thereof and application of nanorod flower-shaped In2O3 material in methane gas sensing detection
Preparation and calcination by hydrothermal method, nanorod-shaped In2O3 material was obtained, which solved the problem of insensitive response of traditional materials to methane gas and significantly improved methane gas sensing performance.
Patent Information
- Application Number
- CN202510274080.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-06-13
AI Technical Summary
The existing metal oxide semiconductor materials have low sensitivity and selectivity to methane gas, making it difficult to meet practical application needs.
Indium hydroxide nanomaterials were prepared by hydrothermal method and calcined at 300-500°C to obtain nanorod flower-shaped In2O3 material, which improved its response performance to methane gas.
The sensitivity and response speed of In2O3 material to methane gas are improved, the response value change range is 1-11, the response time is 120s, the recovery time is 18s, and the response capacity is 1.7-2.0 times.
Smart Images

Figure CN120136157A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal oxide semiconductor materials. Specifically, it relates to an In 2 O 3 material and its preparation method, and the application of this material in gas sensing detection. Background Art
[0002] The incidence of intestinal diseases (such as irritable bowel syndrome, small intestinal bacterial overgrowth, etc.) is on the rise globally, seriously affecting people's health and quality of life. Traditional diagnostic methods for intestinal diseases, such as colonoscopy, fecal occult blood test, etc., have many drawbacks. Colonoscopy is an invasive operation, which not only brings physical pain to patients, but may also cause complications such as infection and intestinal perforation, and the acceptance of patients is relatively low. Although the fecal occult blood test is non-invasive, the test results are easily interfered by factors such as diet and drugs, and the accuracy is difficult to guarantee. In recent years, breath analysis has become a research hotspot due to its non-invasiveness and convenience. Among them, methane (CH 4 ) as a biomarker gas for intestinal flora metabolism, its abnormal concentration is closely related to various intestinal diseases. For example, the methane concentration in the exhaled breath of patients with methane-dominant irritable bowel syndrome (IBS) is significantly increased. It can be seen that developing a rapid diagnostic tool based on exhaled methane detection has important clinical value.
[0003] Metal oxide semiconductor gas sensors have been widely used in the gas sensing field due to their advantages such as low cost, simple preparation, and rapid response. However, traditional metal oxide semiconductor materials have low sensitivity and selectivity to methane gas, which are difficult to meet the actual application requirements. In recent years, nanostructured materials have shown great application potential in the gas sensing field due to their unique physical and chemical properties. Among them, indium oxide (In 2 O 3 ) as a wide-bandgap (3.5 - 3.7 eV) semiconductor material has good gas sensing properties, but its response to methane gas still needs to be further improved. In order to improve the sensing performance of indium oxide to methane gas, researchers have tried various methods, such as doping, compounding, morphology control, etc. Among them, controlling the morphology and microstructure of the material is considered an effective means. Summary of the Invention
[0004] The present invention provides a nano-rod flower-like In 2 O 3 material and its preparation method, and the application of this material in methane gas sensing detection; because the material prepared at a specific annealing temperature has good gas sensing properties to methane gas, it is used to solve the problems of existing methane sensors such as high working temperature, low response value, and difficulty in detecting low concentrations.
[0005] To achieve the above-mentioned invention object, the present invention is realized through the following technical solutions:
[0006] The present invention provides a nano-rod flower-like In 2 O 3 material, which is obtained according to the following preparation method:
[0007] S1: Dissolve indium trichloride tetrahydrate in deionized water and stir vigorously, then add urea and continuously stir until completely dissolved to form a homogeneous mixed solution;
[0008] S2: Carry out a hydrothermal reaction on the mixed solution obtained in S1, and cool to room temperature after the reaction to obtain a white indium hydroxide solid material;
[0009] S3: Centrifuge and wash the white indium hydroxide obtained in S2 with deionized water and ethanol respectively, and collect the washed sample for drying and standby;
[0010] S4: Calcinate the sample obtained in S3 at 300 - 500 °C, and after cooling to room temperature, obtain an In 2 O 3 material with a nano-rod flower-like microstructure.
[0011] According to one aspect of the present invention, a preparation method of a nano-rod flower-like In 2 O 3 material is provided, and it is carried out according to the following steps:
[0012] S1: Dissolve indium trichloride tetrahydrate in deionized water and stir vigorously, then add urea and continuously stir until completely dissolved to form a homogeneous mixed solution;
[0013] S2: Carry out a hydrothermal reaction on the mixed solution obtained in S1, and cool to room temperature after the reaction to obtain a white indium hydroxide solid material;
[0014] S3: Centrifuge and wash the white indium hydroxide obtained in S2 with deionized water and ethanol respectively, and collect the washed sample for drying and standby;
[0015] S4: Calcinate the sample obtained in S3 at 300 - 500 °C, and after cooling to room temperature, obtain an In 2 O 3 material with a nano-rod flower-like microstructure.
[0016] In the above nano-rod flower-like In 2 O 3 material and its preparation method:
[0017] Preferably, in S1, the molar ratio of indium trichloride tetrahydrate to urea is 1:8 - 10.
[0018] Preferably, in S1, the continuous stirring time after adding urea is 30 - 60 min.
[0019] Preferably, in S2, the hydrothermal reaction is carried out in a stainless - steel autoclave with a polytetrafluoroethylene liner; the temperature of the hydrothermal reaction is 120 - 140 °C, and the time is 10 - 15 h.
[0020] Preferably, in S3, the washing method is to wash 3 times each with deionized water and ethanol, and the centrifugation condition is to centrifuge at a speed of 10000 - 12000 rpm for 1 - 2 min.
[0021] Preferably, in S3, the drying condition is to place it in an oven at 60 - 80 °C overnight.
[0022] Preferably, in S4, the calcination time is 2 - 4 h; the calcination is carried out in a tubular furnace, and the heating rate is set at 3 - 5 °C / min.
[0023] According to another aspect of the present invention, there is provided an application of the above - mentioned nanorod - flower - shaped In 2 O 3 material in the methane gas - sensing detection.
[0024] Furthermore, it includes: first, welding a ceramic tube and a heating resistance wire to a base; then taking the nanorod - flower - shaped In 2 O 3 material and dissolving it in deionized water, stirring it with a brush until it becomes a paste; finally, evenly coating the paste on the surface of the ceramic tube and drying it; repeating the operations of coating and drying 3 - 5 times, and obtaining a gas - sensitive element after drying.
[0025] The beneficial effects of the present invention are:
[0026] The present invention provides a preparation method of a novel modified indium oxide gas - sensitive material. First, indium hydroxide nanomaterials are prepared by a hydrothermal method, and then indium oxide nanorod - flower - shaped materials are obtained through high - temperature calcination. The nanorod - flower - shaped structure has a large specific surface area and abundant active sites, which is beneficial to the adsorption and reaction of gas molecules, thereby improving the sensitivity and response speed of the sensor. In addition, the annealing temperature, as a key parameter in the material preparation process, has an important influence on the crystal structure, defect concentration and surface chemical state of the material, and thus affects its gas - sensitive performance.
[0027] After testing, the modified In 2 O 3The material has a three-dimensional hierarchical nanorod flower-like structure. The gas sensor element made from it has excellent sensing performance for methane gas. At an operating temperature of 80 - 400 °C, the response value varies in the range of 1 - 11. Among them, the optimal sample has a response value as high as 11 to 100 ppm of methane gas, a response time of 120 s, and a recovery time of 18 s. Compared with indium oxide gas-sensing materials prepared by other methods, the response ability is increased by 1.7 - 2.0 times.
[0028] The present invention improves the defects of the In 2 O 3 material for methane sensing response, such as insensitive reaction and instability. It has the significant advantages of simple preparation process and low production cost, and shows excellent performance in methane detection. Therefore, it presents broad application prospects in the fields of environmental monitoring and human health monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 X-ray diffraction (XRD) patterns of the nanorod flower-like In 2 O 3 gas-sensing materials with three-dimensional hierarchical structures prepared in Examples 1 - 3.
[0030] Figure 2 For Example 1 ( Figure 2 a - c), 2 ( Figure 2 d - f), 3 ( Figure 2 g - i) Scanning electron microscope (SEM) images of the nanorod flower-like In 2 O 3 gas-sensing materials with three-dimensional hierarchical structures.
[0031] Figure 3 Responses of the sensors assembled with the In 2 O 3 gas-sensing materials prepared in Examples 1 - 3 of the present invention to 100 ppm CH 4 at different operating temperatures.
[0032] Figure 4 Response and recovery curves of the sensor assembled with the In 2 O 3 gas-sensing material prepared in Example 3 of the present invention to 100 ppm methane at 240 °C.
[0033] Figure 5 Stability test of the sensor assembled with the In 2 O 3 gas-sensing material prepared in Example 3 of the present invention to 100 ppm methane at 240 °C. DETAILED DESCRIPTION OF THE INVENTION
[0034] The following will combine the accompanying drawings and embodiments to describe the specific implementation of the present invention in more detail, so as to better understand the solution of the present invention and the advantages of its various aspects. It should be noted that the following described specific implementation manners and embodiments are only for the purpose of illustration, rather than a limitation on the present invention.
[0035] Example 1:
[0036] Step S1: Dissolve 2.5 mmol of InCl 3 ·4H 2 O in 20 mL of deionized water. After vigorous stirring, add 24 mmol of urea and continuously stir until completely dissolved to obtain a uniform indium chloride / urea solution.
[0037] Step S2: Take 20 mL of the uniform indium chloride / urea solution obtained in S1 and transfer it to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave. Perform hydrothermal treatment at 120 °C for 12 h. After the reaction is completed, cool to room temperature to obtain a white indium hydroxide solid.
[0038] Step S3: Centrifuge and wash the white product obtained after the reaction in S2 with deionized water and ethanol three times each. Centrifuge for 2 min under the condition of a rotation speed of 10000 rpm. Place the washed solid product in an oven for drying, and collect the dried product for standby.
[0039] Step S4: Transfer the sample collected in S3 to a tubular furnace and calcine it at 300 °C for 2 h. Set the heating rate to 5 °C / min; name the obtained final product In 2 O 3 -300.
[0040] Example 2:
[0041] Step S1: Dissolve 5 mmol of InCl 3 ·4H 2 O in 40 mL of deionized water. After vigorous stirring, add 48 mmol of urea and continuously stir until completely dissolved to obtain a uniform indium chloride / urea solution.
[0042] Step S2: Take 40 mL of the uniform indium chloride / urea solution obtained in S1 and transfer it to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave. Perform hydrothermal treatment at 130 °C for 12 h. After the reaction is completed, cool to room temperature to obtain a white indium hydroxide solid.
[0043] Step S3: Centrifuge and wash the white product obtained after the reaction in S2 with deionized water and ethanol three times each. Centrifuge for 2 min under the condition of a rotation speed of 11000 rpm. Place the washed solid product in an oven for drying, and collect the dried product for standby.
[0044] Step S4: Transfer the sample collected in S3 to a tubular furnace, calcine at 400 °C for 2 h, and set the heating rate to 5 °C / min; name the final product obtained as In 2 O 3 -300.
[0045] Example 3:
[0046] Step S1: Dissolve 7.5 mmol of InCl3·4H2O in 60 mL of deionized water. After vigorous stirring, add 72 mmol of urea and continuously stir until completely dissolved to obtain a homogeneous indium chloride / urea solution.
[0047] Step S2: Take 40 mL of the homogeneous indium chloride / urea solution obtained in S1 and transfer it to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave. Perform hydrothermal treatment at 140 °C for 12 h. After the reaction is completed, cool to room temperature to obtain a white indium hydroxide solid.
[0048] Step S3: Centrifuge and wash the white product obtained after the reaction in S2 three times each with deionized water and ethanol. Centrifuge for 2 min at a rotation speed of 12,000 rpm. Place the washed solid product in an oven for drying, and collect the dried product for standby.
[0049] Step S4: Transfer the sample collected in S3 to a tubular furnace, calcine at 500 °C for 2 h, and set the heating rate to 5 °C / min; name the final product obtained as In 2 O 3 -300.
[0050] The characterization tests of the nano gas-sensing materials synthesized in the above three examples are as follows:
[0051] Figure 1 For In 2 O 3 -300, In 2 O 3 -400, In 2 O 3 -500, the X-ray diffraction pattern (XRD) was used to test the crystal structure of the prepared nano materials in the range of 20 - 70°. Obviously, obvious diffraction peaks appeared at positions such as 2θ = 30.6°, 35.5°, 51.3°, 60.6°, etc. These diffraction peaks correspond to the (222), (400), (440), and (622) crystal planes of indium oxide respectively. The positions of the characteristic diffraction peaks tested by the characterization results can be compared with In 2 O 3The standard card (PDF#00-006-0416) shows a good match. This is an important basis for determining that the sample is indium oxide. As the calcination temperature increases, it can be found that the diffraction peak position of In 2 O 3 -500 is slightly shifted compared to that of In 2 O 3 -300 and In 2 O 3 -400. This may be due to the lattice distortion or stress within the sample, which causes a change in the lattice constant. The characteristic peaks of the XRD test results are sharp and symmetric, indicating that the prepared rod-flower-shaped In 2 O 3 has good crystallinity integrity.
[0052] Figure 2 shows the scanning electron microscope (SEM) of the In 2 O 3 gas-sensitive material at different calcination temperatures. The results show that at 300 °C calcination, a fine rod-flower-shaped indium oxide structure has formed, and the rod length is about 3 μm. As the temperature increases, the rod-flower-shaped structure aggregates, and the surface of the rod-shaped structure changes from smooth to uneven, and finally cracks appear at the end of the structure at 500 °C. The aggregated structure promotes the increase of the surface active sites of In 2 O 3 and increases the specific surface area of the sample, which is consistent with the XRD characterization results.
[0053] Example 4:
[0054] First, weld the Al 2 O 3 ceramic tube and the heating resistance wire to the base; then take 5 mg each of the prepared In 2 O 3 -300, In 2 O 3 -400, In 2 O 3 -500 gas-sensitive materials are dissolved in a little deionized water and stirred with a brush until it becomes a paste; finally, the paste is evenly coated on the surface of the Al 2 O 3 ceramic tube and placed in an oven at 60 °C for 2 min. Repeat the above operations (coating + drying) 3 - 5 times. After drying, the gas-sensitive test elements are obtained: In 2 O 3 -300 gas-sensitive element, In 2 O 3 -400 gas-sensitive element, In 2 O 3 -500 gas-sensitive element.
[0055] Example 5:
[0056] In this experiment, the performance of the gas sensor was tested using a dynamic gas distribution analysis system. The gas-sensitive component consists of three parts: an Au electrode, an Al 2 O 3 ceramic tube, a nickel-chromium heating resistance wire, and a bakelite base. The gas flow rate is controlled by a precision gas flow controller (MFC), making the test results more reliable. The adjustment of test target gases with different concentrations can be achieved by controlling the flow rates of the target gas and air. The test chamber is connected to a heating device to change the operating temperature (75 - 400 °C) of the gas-sensitive element. The response (S) of the sensor to the target gas is defined as S = Ra / Rg, where Ra and Rg are the sensor resistances in air and the target gas, respectively. The response time (τres) and recovery time (τrecov) are defined as the time required to reach 90% of the total difference in resistance before and after. During the experiment, the ambient temperature was 25 °C - 30 °C, and the relative humidity (RH) was 15% - 30%.
[0057] Figure 3 Shown is the response of In 2 O 3 gas-sensitive elements to methane gas at 75 - 400 °C under different calcination temperatures. As the temperature increases, the samples generally show a trend of first increasing and then decreasing. It is observed that the In 2 O 3 -500 gas-sensitive element has the best response to methane, with an optimal operating temperature of 240 °C, reaching a maximum response value of 11, which is 2 times and 1.7 times the response values of In 2 O 3 -300 and In 2 O 3 -400 at this operating temperature, respectively. And the optimal operating temperature of the In 2 O 3 -500 gas-sensitive element has decreased by about 10 °C compared to others, showing more excellent sensing performance.
[0058] Figure 4 Shown is the response and recovery curve of the In 2 O 3 -500 gas-sensitive element to 100 ppm methane gas at 240 °C. As can be seen from the figure, the response time of this gas-sensitive element is 120 s, and the recovery time is 18 s, showing good response and recovery rates.
[0059] Figure 5 The results of five repeated experiments of the In 2 O 3 -500 gas-sensitive element to 100 ppm methane gas at an operating temperature of 240 °C were studied. The results show that this gas-sensitive element exhibits high stability and strong repeatability.
[0060] In summary, in response to the need for detecting methane gas in exhaled breath for intestinal diseases, the present invention has successfully synthesized nanorod flower-like In 2 O 3 materials, and systematically explored the differences in the methane detection capabilities of In 2 O 3 synthesized at different annealing temperatures. The experimental results show that by regulating the annealing temperature, the crystal structure and surface chemical state of the material can be effectively optimized, thereby significantly improving its sensitivity and selectivity to methane gas. This provides new ideas for the development of high-performance methane gas sensors.
[0061] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above specific embodiments. The above specific embodiments are merely illustrative and not restrictive. Under the inspiration of the present invention, those of ordinary skill in the art can make many specific transformations in form without departing from the spirit of the invention and the scope protected by the claims. All of these fall within the protection scope of the present invention.
Claims
1. A method for preparing nanorod flower-like In2O3 material, characterized in that: Follow these steps: S1: dissolving indium trichloride tetrahydrate in deionized water and stirring vigorously, then adding urea and stirring continuously until it is completely dissolved to form a uniform mixed solution; S2: subjecting the mixed solution obtained in S1 to a hydrothermal reaction, cooling to room temperature after the reaction, and obtaining a white indium hydroxide solid material; S3: The white indium hydroxide obtained in S2 is centrifugally washed with deionized water and ethanol respectively, and the washed samples are collected and dried for later use; S4: The sample obtained in S3 is calcined at 300-500°C and then cooled to room temperature to obtain In2O3 material, whose microscopic morphology is nanorod flower-like.
2. The method for preparing a nanorod flower-like In2O3 material according to claim 1, characterized in that: In S1, the molar ratio of indium trichloride tetrahydrate to urea is 1:8-10.
3. The method for preparing a nanorod flower-like In2O3 material according to claim 1, characterized in that: In S1, the continuous stirring time after adding urea is 30-60 minutes.
4. The method for preparing a nanorod flower-like In2O3 material according to claim 1, characterized in that: In S2, the hydrothermal reaction is carried out in a stainless steel high-pressure reactor lined with polytetrafluoroethylene; the temperature of the hydrothermal reaction is 120-140°C and the time is 10-15h.
5. The method for preparing a nanorod flower-like In2O3 material according to claim 1, characterized in that: In S3, the washing method is to wash with deionized water and ethanol three times each, and the centrifugation condition is to centrifuge at a speed of 10000-12000 rpm for 1-2 minutes.
6. The method for preparing a nanorod flower-like In2O3 material according to claim 1, characterized in that: In S3, the drying condition is to place in an oven at 60-80°C overnight.
7. The method for preparing a nanorod flower-like In2O3 material according to claim 1, characterized in that: In S4, the calcination time is 2-4 hours; the calcination is carried out in a tubular furnace, and the heating rate is set to 3-5°C / min.
8. A nanorod flower-like In2O3 material, characterized in that: The nanorod flower-like In2O3 material is obtained by the preparation method of any one of claims 1-7.
9. Use of the nanorod flower-like In2O3 material as claimed in claim 8 in methane gas sensing.
10. An application of the nanorod flower-like In2O3 material as claimed in claim 9 in methane gas sensing, characterized in that: include: First, the ceramic tube and the heating resistance wire are welded to the base; then the nanorod flower-shaped In2O3 material is dissolved in deionized water and stirred with a brush until it becomes a paste; finally, the paste is evenly coated on the surface of the ceramic tube and dried; the coating and drying operations are repeated 3-5 times, and a gas sensor is obtained after drying.